Real Interest Rate and Saving Behavior in Nepal - Gaire, Hom Nath (Banking Journal, 2012)
Keywords: Real Interest Rate; Bank Deposit; Gross Domestic Saving; Expected Inflation DOI: http://dx.doi.org/10.3126/bj.v2i1.5703 Banking Journal 2012; 2(1): 16-34